1984
DOI: 10.1016/0022-0965(84)90066-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of phonetic memory in disabled and normal readers

Abstract: Development of phonetic memory in disabled and normal readers U n i v e r s i t ä t P o t s d a mHumanwissenschaftliche Fakultät Most contemporary researchers agree that reading is parasitic on language and that individual differences in reading ability are related to differences in language skills (cf. Frith, 1981;Gleitman & Rozin, 1977; Shankweiler & Liberman, 1976; Vellutino, 1977 Vellutino, , 1979. Support for this view has been provided by several recent studies of memory for linguistic stimuli, review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 23 publications
3
32
1
2
Order By: Relevance
“…Hanson, Liberman, and Shankweiler (1984) found repeated rhyming strings to be easier for subjects in a study employing short sequences (four items) with the same stimuli repeated on each trial in varying order. In addition, the "rhyme effect" appears to be sensitive to subject characteristics (Hall et al, 1983) and to age effects (Olson et al, 1984). It is evident that additional work is necessary to understand the basis of the traditional rhyme effect in STM.…”
Section: Resultsmentioning
confidence: 99%
“…Hanson, Liberman, and Shankweiler (1984) found repeated rhyming strings to be easier for subjects in a study employing short sequences (four items) with the same stimuli repeated on each trial in varying order. In addition, the "rhyme effect" appears to be sensitive to subject characteristics (Hall et al, 1983) and to age effects (Olson et al, 1984). It is evident that additional work is necessary to understand the basis of the traditional rhyme effect in STM.…”
Section: Resultsmentioning
confidence: 99%
“…We anticipated that RDs would approach both encoding and choosing from among the response alternatives with more care than the ADDH boys. Reports that RDs are less sensitive than normal children to the acoustic features of rhyming words also suggested that they might engage in less acoustic processing (Mark, Shankweiler, Liberman, & Fowler, 1977;Olson, Davidson, Kliegl, & Davies, 1984). Finally, by questioning subjects about the methods they used to remember the word pairs, we thought we might find evidence that RDs approached the task in a more reflective and effortful manner.…”
Section: Memory Processes In Reading Disabled Children and Possible Amentioning
confidence: 87%
“…They also do not show the phonemic confusability effect (i.e., better memory for phonemically dissimilar vs. rhyming words) that is evident at an early stage in normal readers (Byrne & Shea, 1979;Jorm, 1983;Mann, Liberman, & Shankweiler, 1980), although the effect may emerge in poor readers in early adolescence (Johnston, 1982;Siegel & Linder, 1984). Normal readers show a reduction in phonemic confusability with increasing age, probably because of increased precision of phonemic discrimination (Olson, Davidson, Kliegl, & Davies, 1984). Finally, phoneme segmentation and awareness tasks, as well as rhyming skill, have been shown not only to differentiate good and poor readers (Bradley & Bryant, 1983;Mann, 1984;Share, Jorm, Maclean, & Matthews, 1984;Snowling et aI., 1986;Stanovich, 1988a;Wagner & Torgesen, 1987), but also to be good predictors of future reading ability (Adams, 1990;Goswami, 1990;Mann, 1993;Mann & Brady, 1988;Share et aI., 1984;Stanovich et aI., 1984).…”
Section: Evidence For a Phonemic/phonological Deficiti In Dyslexiamentioning
confidence: 94%